IMPLEMENTASI REAL TIME CLOCK UNTUK PENGATURAN PELAYANAN DAYA OLEH PEMBANGKIT LISTRIK TENAGA SURYA - Muhammad Fadlan Siregar; Suprianto Suprianto (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan)
the implementation of real time clock (RTC) for the regulation of power services by PLTS aims to design the scheduling of power service systems by PLTS using Arduino and RTC so that power services can be optimized while at the same time making savings in electricity bills. The method used is an experimental method that is designing a power service system using Arduino and RTC to get good design results. The equipment used is solar panels, inverters, Arduino, RTC and batteries. The results showed that the implementation of the RTC for the regulation of PLTS power services starts at 17:00 WIB until 05:01 WIB or for 12 hours can serve household electricity needs of 1.887 Kwh, Voltage at 24 volt 100 Ah battery terminals for 12 hours loading down by 1.6 volts from the initial battery voltage of 25.1 volts to the final service voltage of 23.5 volts. Implementation of the RTC for the regulation of PLTS power services starting at 17:00 WIB until 05:01 WIB can save electricity consumption of PLN abouth Rp. 75,928.- per month assuming the electricity price of PLN is Rp. 1352 / Kwh.